Eu venho de Alepo : o discurso (neo)orientalista na (auto)biografia de um refugiado sírio - Souza, Daniele dos Santos de (2018)
Armed conflicts in Syria after the Arab Spring and the humanitarian crisis of refugees have been highlighted in the plot of autobiographies of Syrian refugees in the international publishing market. This dissertation seeks to analyze the (neo) orientalist discourse in the (auto)biography Eu venho de Aleppo of the Syrian refugee Joude Jassouma in order to present possible understandings about the effects produced by world views structured in oppositions like West and East, war and peace, we and the others, civilized and barbaric, among others. The research understands Eu venho de Aleppo as a privileged object of the qualitative approach (DENZIN; LINCOLN, 2006), since the autobiography can allow the researcher to interpret the meanings of a given social phenomenon (DESLAURIERS; KÉRISIT, 2012). The main corpus of the research is constituted by excerpts and images extracted from the book analyzed. The study of discourse is based on the Foucaultian conceptions of discursive formation, enunciation, relations of power, truth and power (Foucault, 2008, 2012) and it is understood as a transdisciplinary and undisciplined research (MOITA LOPES, 2006). The theoretical framework is divided into two parts: Orientalism and the discursive construction of the Other (SAID, 2004, 2011, 2016) and Post / neo-Orientalism: a purgatory state (DABASHI, 2017), which is extanded with discussions related to (neo)orientalism (ABULUGHOD, 2012, BASTOS, 2016, BAUMAN, 2017a, 2017b, COSTA, 2016). The research questions were: 1) how is the relationship between the West and the East discursively constructed in Joude Jassouma's autobiography?, 2) how does (neo) Orientalist discourse manifest in the book? and 3) what are the effects of senses produced? The results suggest that Eu venho de Aleppo joins the (neo) orientalist discursive formation insofar as it builds the West as the space of freedom and peace and the East as the space of war and barbarism. In addition, there is also the pedagogical character directed to the Western reader, the main public of books like this. The effects of sense produced are diverse, for while thought systems such as (neo) Orientalism reinforce structural violence and marginalize other ways of life, the question of refuge can encourage voluntary solidarity.